Complex Laparoscopic Myomectomy with Severe Adhesions Performed with Proper Preventive Measures and Power Morcellation Provides a Safe Choice in Certain Infertility Cases - Jaime Alfaro-Alfaro; María de los Ángeles Flores-Manzur; Roberto Nevarez-Bernal; Rodrigo Ayala-Yáñez (Hindawi Limited, 2016)
Laparoscopic myomectomy offers a real benefit to infertile patients with uterine fibroids and peritoneal adhesions. The procedure requires a skilled surgeon and laparoscopy technique to minimize adhesion formation and other proven benefits. Restrictions arise since this procedure requires power morcellation for fibroid tissue extraction. Two years ago, the Food and Drug Administration in the United States of America (FDA) issued the alert on power morcellation for uterine leiomyomas, addressing the risk of malignant cell spreading within the abdominal cavity (actual risk assessment from 1 in 360 to 1 in 7400 cases). We review a 30-year-old female, without previous gestations, hypermenorrhea, intermenstrual bleeding, and chronic pelvic pain. Transvaginal ultrasound reports multiple fibroids in the right portion of a bicornuate uterus. Relevant history includes open myomectomy 6 years before and a complicated appendectomy, developing peritonitis within a year. Laparoscopy revealed multiple adhesions blocking uterine access, a bicornuate uterus, and myomas in the expected site. Myomectomy was performed utilizing power morcellation with good results. FDA recommendations have diminished this procedure's selection, converting many to open variants. This particular case was technically challenging, requiring morcellation, and safety device deployment was impossible, yet the infertility issue was properly addressed. Patient evaluation, safety measures, and laparoscopy benefits may outweigh the risks in particular cases as this one.